Leitliniengerechte psychiatrisch-psychotherapeutische Krankenhausbehandlung: normative Personalermittlung am Beispiel Depression = Guideline-adherent psychiatric-psychotherapeutic hospital care : normative definition of staff required using the example of depression - Berger, Matthias; Herpertz, Sabine (Der Nervenarzt, 2015)
SummaryBackgroundUnipolar depression is of high relevance in German inpatient treatment. An effective psychiatric psychotherapeutic hospital treatment also requires sufficient staff for carrying out psychotherapeutic treatment.Aims and objectivesThe aim of this study was to define the staff requirements for guideline-adherent psychiatric-psychotherapeutic inpatient treatment of depression on the basis of a weekly treatment schedule for a 5-week admission period. A further aim was to compare the staff required with the resources defined by the German psychiatric staffing regulations (Psych-PV).Material and methodsThe weekly schedule was normatively defined on the basis of the current evidence for treatment efficacy and effectiveness. The staff required was calculated on the basis of the weekly schedule. The time for psychotherapy defined by the Psych-PV was calculated using the treatment classification provided by a large nationwide database. ResultsRegarding psychotherapy, 280 min per week is regarded as necessary and usually sufficient according to the current evidence. The results showed clearly higher requirements of working time of psychiatrists and psychologists than those defined by the Psych-PV. In particular, the Psych-PV allows only 72 min for psychotherapy per patient and week and only a limited amount of direct patient contact with psychiatrists.ConclusionThe figures provided impressively show that the Psych-PV does not allow effective guideline-adherent hospital treatment within a reasonable length of hospital stay. Despite its evidential effectiveness, psychotherapeutic treatment cannot be sufficiently provided under the current financing circumstances.